2019
DOI: 10.1136/bcr-2019-229622
|View full text |Cite
|
Sign up to set email alerts
|

Parvoviral infection with systemic impact and renal consequences

Abstract: Parvovirus infection is usually asymptomatic especially in immunocompetent adults. When symptomatic it can range from mild to life threatening depending on the patient’s age and comorbidities. We report a case of a 40-year-old male patient with parvovirus infection who presented a purpuric rash in distal extremities, acute kidney injury, type II mixed cryoglobulinaemia and hypocomplementaemia. His renal biopsy showed a mesangioproliferative glomerulonephritis with positive immunoreactivity to C3, IgM and C1q. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Clinical studies have shown that the disease is an allergic reaction caused by bacteria, such as Legionella or Salmonella, viruses such as rubella virus or varicella virus, parasites such as roundworm and Mycoplasma, etc. [ 11 , 12 ]. Failure to effectively control the disease severely impacts renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that the disease is an allergic reaction caused by bacteria, such as Legionella or Salmonella, viruses such as rubella virus or varicella virus, parasites such as roundworm and Mycoplasma, etc. [ 11 , 12 ]. Failure to effectively control the disease severely impacts renal function.…”
Section: Discussionmentioning
confidence: 99%